Does retirement kill you? Evidence from early retirement windows - Norma B. Coe; Maarten Lindeboom (Institute for the Study of Labor (IZA), 2008)
The magnitude of the effect that health has on the retirement decision has long been studied. We examine the reverse relationship, whether or not retirement has a direct impact on later-life health. In order to identify the causal relationship, we use unexpected early retirement window offers to instrument for retirement behavior. They are legally required to be unrelated to the baseline health of the individual, and are significant predictors of retirement. We find that there is no negative effect of early retirement on men's health, and if anything, a temporary increase in self-reported health and improvements in health of highly educated workers. While this is consistent with previous literature using Social Security ages as instruments, we also find some evidence that anticipation of retirement might also be important, and might bias the previous estimates towards zero.
urn:nbn:de:101:1-20081127421
Keywords: I12; 330; Health; retirement; instrument; causal effect; Flexible Altersgrenze; Gesundheit; Sterblichkeit; Alte Menschen; USA